Ischemic strokes in COVID-19: risk factors, obesity paradox, and distinction between trigger and causal association - Janes, Francesco; Sozio, Emanuela; Gigli, Gian Luigi; Ripoli, Andrea; Sbrana, Francesco; Kuris, Fedra; Nesi, Lorenzo; Semenzin, Tosca; Bertolino, Giacomo; Deana, Cristian; Bagatto, Daniele; Ciardi, Chiara; et al. (Frontiers in Neurology, 2023)
Background and purpose Stroke has been described as a COVID-19 complication. However, its occurrence rate, risk factors, and causal relationships are still not well established. Methods We describe the characteristics of confirmed COVID-19-related strokes among all cases of COVID-19 hospitalized in our health network, from November 1, 2020 to April 30, 2021. Risk factor analysis has been conducted for ischemic stroke (IS), which represents 92% of all confirmed cases of Covid-19-related strokes, and a “causal attribution to infection” classification is provided. Results In all, 62/4105 hospitalized COVID-19 patients had an acute stroke (1.51%). Severe COVID-19 (OR 2.27—CI 1.06–4.77; p = 0.032), atrial fibrillation (OR 3.65—CI 1.63–7.98; p = 0.001), and ischemic heart disease (OR 4.590—CI 1.714–12.137; p = 0.002) proved to be independent risk factors for IS, while obesity was a protective factor (OR 0.90—CI 0.82–0.97; p = 0.012). COVID-19 had a causal role in 32.1% of IS cases, was a relevant cofactor in 28.6% of cases of IS, and was a possible trigger in 39.3% of events. Conclusion Our stroke occurrence rate is consistent with other population-based reports (range 0.34–2.7%). Prespecified peculiar clinical and radiological features allow the distinction between “IS caused by COVID-19” and “IS triggered by COVID-19.” Clinical history of vascular diseases and risk factors is crucial in determining the risk of IS in patients with COVID-19. However, the protective effect of a BMI > 30 kg/m2 seems to suggest an obesity paradox.